Amygdala/hippocampal activation during the menstrual cycle: Evidence for lateralization of effects across different tasks. (January 2015) - Lisofsky, Nina; Lindenberger, Ulman; Kühn, Simone
Abstract: Variations in hormonal levels between the follicular and the luteal phase of the female menstrual cycle are associated with variations in emotional and cognitive aspects of behavior. The functional neural correlates of these cycle-related variations have been explored in previous neuroimaging studies. We summarize the existing findings of functional magnetic resonance imaging (fMRI) studies to identify regions of increased brain activation in the follicular or luteal phases of the cycle that are concordant across studies. Eleven fMRI studies reporting coordinates of higher brain activation in one of the two main cycle phases were included in the analysis. Activation likelihood estimation was used to determine concordance. We found higher left amygdala/hippocampal activation during the luteal phase and higher right amygdala/hippocampal activation during the follicular phase. Additionally, the anterior cingulate cortex and temporal pole showed increased activation during the luteal phase and the superior temporal gyrus during the follicular phase. The observed pattern of cycle-dependent functional lateralization of the amygdala/hippocampal complex is consistent with findings on cycle-related behavioral variations and on sex differences in lateralization of activity in amygdala and hippocampus. Highlights: Functional neural brain activity of women differs between cycle phases. In line with previous research, amygdala and hippocampal lateralization seems to be affected. Those findings should be taken into account in fMRI research including women.